Review of the genus Pseudognaptorina Kaszab from China (Coleoptera, Tenebrionidae) - Liu, Hao-Yu; Ren, Guo-Dong (Zootaxa, 2009)
The genus Pseudognaptorina Kaszab is reviewed. A new species is described: P. flata sp. nov. from Sichuan, China. A key to the known species is given along with a distribution map.